Kepatuhan Syariah terhadap Praktik Jual Beli Mobil Bekas Kecelakaan - Muhammad Ghibral Thoriq 'Izzatulloh; Sandy Rizki Febriadi; Neng Dewi Himayasari (Bandung Conference Series: Sharia Economic Law)
Abstract. The sale and purchase of accident-damaged used cars may create information asymmetry when the condition of the vehicle is not fully disclosed to prospective buyers. This study aims to analyze the implementation of Sharia Compliance in the sale and purchase of accident-damaged used cars at Showroom JP Accesories, Bandung, based on the principles of transparency, honesty (ṣidq), and justice ('adl). This research employed an empirical juridical approach using a case study method. Data were collected through semi-structured interviews, observation, and documentation and analyzed using descriptive qualitative methods based on Islamic commercial law principles and DSN-MUI Fatwa Number 110/DSN-MUI/IX/2017 concerning Sale and Purchase Contracts. The findings indicate that the sales practices at Showroom JP Accesories generally comply with the principles of Sharia Compliance. Transparency is reflected in the disclosure of vehicle history and condition, honesty is demonstrated by the absence of tadlīs (fraudulent concealment), while justice is reflected in proportional pricing, opportunities for vehicle inspection before the contract, and post-sale warranties. The study concludes that transparency, honesty, and justice are the key factors in achieving Sharia-compliant practices in the sale and purchase of accident-damaged used cars. Abstrak. Praktik jual beli mobil bekas kecelakaan berpotensi menimbulkan asimetri informasi apabila kondisi kendaraan tidak disampaikan secara terbuka kepada calon pembeli. Penelitian ini bertujuan menganalisis penerapan sharia compliance pada praktik jual beli mobil bekas kecelakaan di Showroom JP Accesories Kota Bandung berdasarkan prinsip transparansi, kejujuran (ṣidq), dan keadilan ('adl). Penelitian menggunakan pendekatan yuridis empiris dengan metode studi kasus. Data diperoleh melalui wawancara semi-terstruktur, observasi, dan dokumentasi, kemudian dianalisis secara deskriptif kualitatif berdasarkan prinsip fikih muamalah dan Fatwa DSN-MUI Nomor 110/DSN-MUI/IX/2017 tentang Akad Jual Beli. Hasil penelitian menunjukkan bahwa praktik jual beli di Showroom JP Accesories secara umum telah memenuhi prinsip sharia compliance. Transparansi diterapkan melalui penyampaian riwayat dan kondisi kendaraan, kejujuran ditunjukkan dengan tidak ditemukannya praktik tadlīs, sedangkan keadilan diwujudkan melalui penetapan harga yang proporsional, kesempatan pemeriksaan kendaraan sebelum akad, dan pemberian garansi. Penelitian ini menyimpulkan bahwa penerapan transparansi, kejujuran, dan keadilan menjadi faktor utama dalam mewujudkan praktik jual beli mobil bekas kecelakaan yang sesuai dengan prinsip kepatuhan syariah.